2013
DOI: 10.1128/mcb.00763-12
|View full text |Cite
|
Sign up to set email alerts
|

Stress Granules Inhibit Apoptosis by Reducing Reactive Oxygen Species Production

Abstract: Cells can undergo two alternative fates following exposure to environmental stress: they either induce apoptosis or inhibit apoptosis and then repair the stress-induced alterations. These processes minimize cell loss and prevent the survival of cells with aberrant DNA and protein alterations. These two alternative fates are partly controlled by stress granules (SGs). While arsenite, hypoxia, and heat shock induce the formation of SGs that inhibit apoptosis, X-ray irradiation and genotoxic drugs do not induce S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
213
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(232 citation statements)
references
References 27 publications
13
213
1
5
Order By: Relevance
“…The truncated form of G3BP1 lacking the NTF2-like N-terminal domain does not induce SGs, as previously observed (14,16). In both single-cycle and multiple-cycle infections, G3BP1 expression caused a potent antiviral effect ranging between 1-and 3-log-unit reduction of virus output compared to the GFP control in all three enteroviruses tested (Fig.…”
Section: G3bp1 and G3bp1-induced Sgs Restrict Enterovirus Infectionsupporting
confidence: 52%
See 1 more Smart Citation
“…The truncated form of G3BP1 lacking the NTF2-like N-terminal domain does not induce SGs, as previously observed (14,16). In both single-cycle and multiple-cycle infections, G3BP1 expression caused a potent antiviral effect ranging between 1-and 3-log-unit reduction of virus output compared to the GFP control in all three enteroviruses tested (Fig.…”
Section: G3bp1 and G3bp1-induced Sgs Restrict Enterovirus Infectionsupporting
confidence: 52%
“…Depletion of G3BP1 inhibits SG formation in response to several stressors (10,12,14), and overexpression of G3BP1 nucleates SG formation independently of additional stressors (2,14,15). We previously reported that large G3BP1-induced SGs, but not small granules, are capable of triggering eIF2␣ phosphorylation through PKR, resulting in translational repression (15).…”
mentioning
confidence: 99%
“…However, others have reported that stress granules can form in the presence of H 2 O 2 in an eIF2␣-independent manner (44,92 Stress granule formation reduces the development of reactive oxygen species, thereby inhibiting apoptosis and favoring repair (93). The YB-1 protein has been proposed to play a key role in translation regulation by interacting with quadruplexes.…”
Section: Discussionmentioning
confidence: 99%
“…SYNTHÈSE REVUES la séquestration des protéines pro-oxydantes (comme G3BP1) dans les granules de stress [49]. L'inhibition pharmacologique de HRI pourrait alors, en empêchant la formation des granules de stress suite aux traitements thérapeutiques, favoriser la surproduction des ROS létales, sensibilisant ainsi les tumeurs résistantes à la mort cellulaire.…”
Section: Gfp-hri G3bpunclassified